The impact of user- and system-initiated personalization on the user experience at large sports events. (May 2016) - Sun, Xu; May, Andrew; Wang, Qingfeng
Abstract: This article describes an experimental study investigating the impact on user experience of two approaches of personalization of content provided on a mobile device, for spectators at large sports events. A lab-based experiment showed that a system-driven approach to personalization was generally preferable, but that there were advantages to retaining some user control over the process. Usability implications for a hybrid approach, and design implications are discussed, with general support for countermeasures designed to overcome recognised limitations of adaptive systems. Highlights: Personalized mobile content improves spectator UX at large sports events. User and system-initiated personalization approaches each provide distinct benefits. User initiated personalization provides accuracy and a feeling of control. System-initiated approaches minimise interaction effort from participants. An integrated hybrid approach can capitalise on the merits of both approaches.